Axiologies in cartoon reading activities - Malinoski Pianaro Angelo, Cristiane; Gumieiro Vieira, Flávia (The ESPecialist, 2023)
Based on the axiological concepts of language of the Bakhtin Circle, this article aims to present proposals for expanding the activities of reading a cartoon, present in a textbook for Youth and Adult Education - EJA, in order to expand awareness students' socioideology. This is qualitative research, with an interpretative, descriptive and propositional approach, since it analyzes the textbook proposals and presents suggestions for expanding the activities, considering the axiological concepts – extraverbal context, intonation and value judgments. It is considered that reading expansion activities can provoke reflection on the social axiologies inherent in discursive practices, focusing on the understanding of live and valued discourse in the classroom and allowing reading to be constituted as an act of ethical responsibility, for qualitative changes in social reality.